Effects of microRNAs on angiogenesis in diabetic wounds - Lyttle, Bailey D.; Vaughn, Alyssa E.; Bardill, James R.; Apte, Anisha; Gallagher, Lauren T.; Zgheib, Carlos; Liechty, Kenneth W. (Frontiers in Medicine, 2023)
Diabetes mellitus is a morbid condition affecting a growing number of the world population, and approximately one third of diabetic patients are afflicted with diabetic foot ulcers (DFU), which are chronic non-healing wounds that frequently progress to require amputation. The treatments currently used for DFU focus on reducing pressure on the wound, staving off infection, and maintaining a moist environment, but the impaired wound healing that occurs in diabetes is a constant obstacle that must be faced. Aberrant angiogenesis is a major contributor to poor wound healing in diabetes and surgical intervention is often necessary to establish peripheral blood flow necessary for healing wounds. Over recent years, microRNAs (miRNAs) have been implicated in the dysregulation of angiogenesis in multiple pathologies including diabetes. This review explores the pathways of angiogenesis that become dysregulated in diabetes, focusing on miRNAs that have been identified and the mechanisms by which they affect angiogenesis.